Bodies, Natures, Origins: Simians and the Biopolitics of the African "AIDS Belt" - Bresalier, Michael (UnderCurrents: Journal of Critical Environmental Studies, 1995)
In a short, prescient discussion towards the end of the first volume of The History of Sexuality, Michel Foucault considers the appearance of biopolitics within the domains of Western modernity. [...]